The Political Economy of Empire in the Early Modern World
XIV, 241 p.
Keywords: This collection of essays draws on fresh readings of classic texts as well as rigorous research in the archives of Europe's greatest imperial power. Its contributors paint a powerful picture of the nature and implementation of political economy in the long eighteenth century, from the East to the West Indies.